Cognitive Bias and Therapy Choice in Breast Reconstruction Surgery Decision-Making. Issue 4 (31st January 2022) - Whyte, Stephen; Bray, Laura; Chan, Ho Fai; Chan, Raymond J.; Hunt, Jeremy; Peltz, Tim S.; Dulleck, Uwe; Hutmacher, Dietmar W.
Abstract : Background: Understanding how medical experts and their patients process and transfer information is of critical importance for efficient health care provision. Behavioral economics has explored similar credence markets where economic incentives, information asymmetry, and cognitive bias can impact patient and surgeon choice. The aim of the current study is to explore how framing and behavioral bias affect elective restorative surgery decision-making, such as breast reconstruction following cancer treatment. Methods: The authors' study uses a cross-sectional survey data set of specialist surgeons ( n = 53), breast care nurses ( n = 101), and former or current breast cancer patients ( n = 689). Data collected include participant demographics, medical history, a battery of cognitive bias tests, and a behavioral framing experiment. Results: This study finds statistically significant differences in breast reconstruction surgery preference by patients and nurses when decision options are framed in different ways (i.e., positively versus negatively). The authors' analysis of surgeons, nurses, and patients shows no statistically significant difference across eight common forms of cognitive bias. Rather, the authors find that the behavioral biases are prevalent to the same extent in each group. This may indicate that differences in experience and education seem not to mitigate biases that may affect patient choices and medical professional's recommendations. The authors' multivariate analysis identifies patient age ( p < 0.0001), body mass index, and self-perceived health ( p < 0.05) as negative correlates for choice of implant-based reconstruction. Conclusion: For surgeons, nurses, and patients, the authors find uniform evidence of cognitive bias; more specifically, for patients and nurses, the authors find inconsistency in preference for type of surgical therapy chosen when alternative procedures are framed in different ways (i.e., framing bias).